Morte de Deus na filosofia de Nietzsche: contribuições de uma perspectiva pós-metafísica para pensar a linguagem da religião - Silva, André Luiz Alves da (2023)
This work aims to contribute with a reflection about the language of religion in a post-metaphysical perspective. It starts with the sentence pronounced by Nietzsche about the death of God, here seen as a metaphor that the philosopher used to refer to an event in Western human culture. Its senses are described as a distrust of the belief in truth and metaphysics, as foundations of moral values and peremptory rational concepts. Nietzsche’s criticism of the Christian religion is considered in its specificity in the philosopher’s writings in which he attacks the values engendered in it that, in his view, deny life in the name of belief in truth. At the end, we return to a text from Nietzsche’s youth in which skepticism about truth appears in the form of an analysis of language as metaphor. It is because language does not correspond to the literality of original experiences that truth turns out to be fictional, in other words, language is metaphor. Nietzsche’s influence was felt in theologians and philosophers of the 20th century, who positively received his sentence and used it to understand religion as language. If religion is language, its language is also metaphor. Therefore, in conclusion, a philosophy of religion is proposed in a post-metaphysical perspective that considers religion in this sense.(AU)